MICRO AND MACROSCOPIC MODELS OF ROCK FRACTURE - Turcotte D.L.; Shcherbakov R.; Newman W.I. (My University, 2003)
The anelastic deformation of solids is often treated using continuum damage mechanics. An alternative approach to the brittle failure of a solid is provided by the discrete fibre-bundle model. Here we show that the continuum damage model can give exactly the same solution for material failure as the fibre-bundle model. We compare both models with laboratory experiments on the time-dependent failure of chipboard and fibreglass. The power-law scaling obtained in both models and in the experiments is consistent with the power-law seismic activation observed prior to some earthquakes.
Keywords: critical point; damage mechanics; fibre-bundle model; fracture; power-law scaling